The Nuclearization of Iran: The America's Responses and Reactions - Darouiche, Ilham; Medjour, Nihal (جامعة الوادي - University of Eloued, 2023)
الملخص: بدأ الصراع بين إيران والولايات المتحدة حول برنامج إيران النووي مع معاهدة حظر انتشار الأسلحة النووية الإيرانية. وقد جادلت طهران بأن الأسلحة النووية تتعارض مع دين الإسلام ومع ذلك ، فقد تغيرت وجهة النظر هذه للتركيز على الأغراض السلمية وحاجة طهران للأسلحة النووية. استخدمت الولايات المتحدة نهجين رئيسيين لوقف البرنامج النووي الإيراني: العقوبات الاقتصادية التي تركز على الطاقة والتمويل والمشاركة الدبلوماسية من خلال المفاوضات واتفاقية العمل الشاملة المشتركة في عام 2015. على الرغم من الاختلافات بينهما ، فقد أدى كلا النهجين إلى تأخير طموحات إيران النووية، حيث تلعب العقوبات الاقتصادية دوراً حاسما في دفع إيران نحو التواصل الدبلوماسي مع الولايات المتحدة . Abstract: Iran's relationship with the United States has been under tension in recent years because of Iran's intentions toward nuclearization. Iran signed the Nonproliferation Treaty and claimed that its nuclear activities were for peaceful and scientific purposes. When America realized its real intent, it started to respond and react in order to cease it. This study aims to offer an overview of the timeline of Iran's nuclear program, its motivations, the United States responses and reactions, and compare the effectiveness of diplomatic engagement with economic sanctions. This study suggests that the inquiry may have an impact on political decisions regarding how to deal with Iran's nuclear program. A qualitative methodology combining historical, descriptive, analytical, and comparative methods is used in this work. The study demonstrates that the development of the nuclear program in Iran is influenced by security concerns, domestic political priorities, Iran's interests, West-Middle East relations, Iraq chemical attacks, and Iran's economy. America has used two approaches to ending the program. First, economic sanctions through financial and energy, which have effects on the economy, humanitarians, and politics Second, diplomatic engagement through negotiations and the Joint Comprehensive Plan of Action Agreement, which has the effect of obstructing Iran's nuclear developments. Consequently, these strategies combined to delay Iran's nuclear program but were unable to stop it.
Literature and Civilization
Keywords: البرنامج النووي الايراني، العقوبات الاقتصادية، المشاركة الديبلوماسية، اتفاقية العمل الشاملة المشتركة; Diplomatic engagement, Economic sanctions, JCPOA, The nuclear program of Iran,US responses and reactions.